The Effect of Health Promotion Program for Patients of Diabetes Mellitus at Dongbang Health Promoting Hospital, Muang District, Ubon Ratchathani Province - โกศัลวิตร, ฐิติมา; กันยะกาญจน์, กัญญารัตน์; บุญญนิวารวัฒน, นฤมล; ศรีธรรมา, ธิดารัตน์ (Journal of Ratchathani Innovative Health Sciences, 2019)
The purpose of this quasi–experimental research was to study effectiveness of health promotion program for patients with Diabetes Mellitus at Dongbang Health Promoting Hospital, Muang District, Ubon Ratchathani Province.The sample consisted of 30 diabetics. The program was applied from Pender’s health promotion model. The experimental group had health promotion program. The duration of program implementation was 12 weeks. The instruments used in this research were health promotion program based on Pender’s concept. The methods used were a visual slide display, a good model presentation, a training demonstration, a self-caring handbook, and focus group. instrument consisted of questionnaire about health promoting behaviors. The Cronbach’s alpha reliability was 0.88. The collected data were analyzed by using percentage, mean, standard deviation and paired t-test. The study results were as follows : After the health promoting behavior program, the Patients DM had better health behaviors than before the health promoting behavior program with statistically significant ( t = 20.10, p<.001).The Mean of FBS was decrease after the program. The program had increased positive health promoting behavior.